Lending appraisal and performance of SACCOS in Rukiga district, Uganda - Moses, Agaba; John Bosco, turyasingura; Jesse David, Kabagambe (African Journal of Business Management, 2023)
This study's objective was to assess how lending appraisal affected SACCO performance in the District. The study's outcome variables were the performance of SACCOs, with SACCO governance serving as a predictor variable. The investigation was preceded by a cross-sectional survey. Data from 5 SACCOs with 109 respondents were collected, and both quantitative and qualitative analyses were merged. The analysis was conducted at three levels, namely: Descriptive, bivariate and multivariate analyses. Since descriptive analysis entailed description of a single variable and its attributes, frequency tables were used to present the data. At the bivariate level, a Pearson correlation matrix was conducted to ascertain the relationships between the predictor variables and the dependent variable. The dependent variable was regressed against using the updated predictor variables for loan approval at the multivariate level (performance of SACCOs). A linear regression model was used to fit the data. According to study findings from the regression model, loan appraisal (coef. = -0. 635, p-value=0.000) have a positive influence on the performance of SACCO in District. This study's main finding is that corporate governance has a big impact on SACCOS performance. The study consequently advises that more emphasis should be given to implementing corporate governance in order to ensure good performance of SACCOs in Rukiga District.